Highly variable upper and abyssal overturning cells in the South Atlantic - Kersale, Marion (2020)
The Meridional Overturning Circulation (MOC) is a primary mechanism driving oceanic heat redistribution on Earth, thereby affecting Earth's climate and weather. However, the full-depth structure and variability of the MOC are still poorly understood, particularly in the South Atlantic. This study presents unique multiyear records of the oceanic volume transport of both the upper (<~3100 meters) and abyssal (>~3100 meters) overturning cells based on daily moored measurements in the South Atlantic at 34.5°S. The vertical structure of the time-mean flows is consistent with the limited historical observations. Both the upper and abyssal cells exhibit a high degree of variability relative to the temporal means at time scales, ranging from a few days to a few weeks. Observed variations in the abyssal flow appear to be largely independent of the flow in the overlying upper cell. No meaningful trends are detected in either cell.